ILLEGAL MIGRANT CRISIS IN GREECE AND TÜRK?YE THROUGH THE MEDITERRANEAN SEA - Rofif Hudzon, Muhammad; Seniwati, Seniwati (SIGNIFICANT : Journal Of Research And Multidisciplinary, 2025)
Irregular migration becomes the most pressing humanitarian & political issue in the Eastern Mediterranean, Turkey-Greece 2022-2024, the increasing flow of migrants (driven by conflict, poverty, and limited legal migration channels) has subjected both countries to overlapping security, legal, and humanitarian pressures. The research examines the crisis through two theoretical lenses: Regional Security Complex Theory (RSCT) and the Human Security Framework. Based on recent data, legal cases, and institutional reports, the study highlights persistent abuses such as expulsions, limited asylum protection, and the abuse of geopolitical leverage, especially under the EU-Turkey Statement and Greece's “safe third country” designation. Despite some examples of cooperation, securitized responses continue to dominate, enabling smuggling networks and putting migrants at great risk. The paper concludes that tackling irregular migration requires moving beyond reactive policies towards sustainable solutions rooted in regional cooperation, legal integrity and the fulfillment of human security. Only through this integrated approach can the region move from managing symptoms to addressing the root causes of migration.